2012
DOI: 10.3329/cardio.v4i2.10458
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation of Left Free Wall Accessory Pathways: Comparison Between Retrograde and Transeptal Approach

Abstract: Study Method:Sixtyn consecutive patients were included in this study, among 44 were male, with a mean age of 35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Male to female ratio was roughly 2:3. Presenting complaints included palpitation (61, 92.4%), dyspnoea (40, 60.6%), chest pain (23, 34.8%), dizziness (8,12.1%) and syncope (7, 10.6%). The mean heart rate during SVT was 161±16 beats/ min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male to female ratio was roughly 2:3. Presenting complaints included palpitation (61, 92.4%), dyspnoea (40, 60.6%), chest pain (23, 34.8%), dizziness (8,12.1%) and syncope (7, 10.6%). The mean heart rate during SVT was 161±16 beats/ min.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical presentation were similar in two other studies. 12,13 Among the CAD risk factors, incidence of smoking was highest in both groups followed by hypertension. Bukkapatnam et al on the contrary, found hypertension as the most prevalent risk factors in both groups.…”
Section: Discussionmentioning
confidence: 99%